Sequence-specific nucleic acid detection from binary pore conductance measurement - Esfandiari, Leyla (2012)
We describe a platform for sequence-specific nucleic acid (NA) detection utilizing a micropipette tapered to a 2 μm diameter pore and 3 μm diameter polystyrene beads to which uncharged peptide nucleic acid (PNA) probe molecules have been conjugated. As the target NAs hybridize to the complementary PNA-beads, the beads acquire negative charge and become electrophoretically mobile. An applied electric field guides these NA-PNA-beads toward the pipette tip, which they obstruct, leading to an indefinite, electrically detectable, partial blockade of the pore. In the presence of non-complementary NA, even to the level of single base mismatch, permanent pore blockade is not seen. We show application of this platform to detection of the anthrax lethal factor sequence.